KEMAMPUAN BAKTERI ASAM LAKTAT YANG DIISOLASI DARI AIR SUSU IBU DALAM MENURUNKAN KADAR KOLESTEROL DARAH TIKUS PUTIH GALUR WISTAR - Dwi Ariesta Wijaya Putra; Semadi Antara; Komang Ayu Nocianitri (Media Ilmiah Teknologi Pangan (Scientific Journal of Food Technology), 2019)
Bile salt hydrolase (BSH) is one of the enzymes produced by lactic acid bacteria. This enzyme has theability to lower cholesterol levels in vitro and in vivo. The lactic acid bacteria used in this study wereL. plantarum I A1, L. plantarum I A8, L. plantarum I B8, L.rhamnosus A6 and L. rhamnosus B10b whicha probiotic candidate isolated from breast milk. The purpose of this study was to determine the activityof BSH and the ability to lower cholesterol both in vitro and in vivo. Three stages of experiment weredone. BSH activity and its ability in decreasing cholesterol in vitro were done for all strains ofLactobacillus. The best strain is L. plantarum I B8 was continued for further experiment to determineits ability to decrease blood cholesterol in in vivo using Wistar Rats.In vivo test results showed that L.plantarum I B8 decreased total cholesterol, LDL, triglyceride, and HDL by 27%, 21%, 29% and 35%respectively.